Mitochondrial genome structural variants and candidate cytoplasmic male sterility-related gene in sugarcane - Yihan Li; Shuangyu Li; Xiuting Hua; Yi Xu; Shuqi Chen; Zehuai Yu; Gui Zhuang; Yuhong Lan; Wei Yao; Baoshan Chen; Muqing Zhang; Jisen Zhang (BMC Genomics)
Abstract Background Sugarcane is a crucial crop for both sugar and bioethanol production. The nobilization breeding and utilization of wild germplasm have significantly enhanced its productivity. However, the pollen sterility in Saccharum officinarum restricts its role to being a female parent in crosses with Saccharum spontaneum during nobilization breeding, resulting in a narrow genetic basis for modern sugarcane cultivars. Mitochondria, often referred to as the intracellular “energy factories”, provide energy for plant life activities, and are also implicated in cytoplasmic male sterility (CMS). Results We performed mitochondrial genome assembly and structural analysis of two Saccharum founding species. We discovered that the proportions of repeat sequences are the primary factor contributing to the variations in mitochondrial genome structure and size between the two Saccharum species. Heterologous expression of the mitochondrial chimeric gene ORF113, which is highly expressed in male-sterile S. officinarum flowers, significantly inhibits growth and ATP synthesis in yeast cells, making it a key candidate CMS-related gene in sugarcane. Furthermore, we developed two co-dominant simple sequence repeat (SSR) markers based on the mitochondrial genome, which can effectively distinguish the cytoplasmic types of the two Saccharum species. Conclusion In this study, we identified structural variants and developed SSR molecular markers in the mitochondrial genomes of both S. officinarum and S. spontaneum. We also identified a novel mitochondrial chimeric ORF as a key candidate CMS-related gene. These findings offer valuable insights into variety identification, genetic resource development, and cross-breeding strategies in sugarcane.